Low incidence and transient elevation of autoantibodies post mRNA COVID-19 vaccination in inflammatory arthritis. (28th May 2022) - Blank, Rebecca B; Haberman, Rebecca H; Qian, Kun; Samanovic, Marie; Castillo, Rochelle; Jimenez Hernandez, Anthony; Vasudevapillai Girija, Parvathy; Catron, Sydney; Uddin, Zakwan; Rackoff, Paula; Solomon, Gary; Azar, Natalie; et al.
Abstract: Objectives: Autoantibody seroconversion has been extensively studied in the context of COVID-19 infection but data regarding post-vaccination autoantibody production is lacking. Here we aimed to determine the incidence of common autoantibody formation following mRNA COVID-19 vaccines in patients with inflammatory arthritis (IA) and in healthy controls. Methods: Autoantibody seroconversion was measured by serum ELISA in a longitudinal cohort of IA participants and healthy controls before and after COVID-19 mRNA-based immunization. Results: Overall, there was a significantly lower incidence of ANA seroconversion in participants who did not contract COVID-19 prior to vaccination compared with those who been previously infected (7.4% vs 24.1%, P = 0.014). Incidence of de novo anti-CCP seroconversion in all participants was low at 4.9%. Autoantibody levels were typically of low titre, transient, and not associated with increase in IA flares. Conclusions: In both health and inflammatory arthritis, the risk of autoantibody seroconversion is lower following mRNA-based immunization than following natural SARS-CoV-2 infection. Importantly, seroconversion does not correlate with self-reported IA disease flare risk, further supporting the encouragement of mRNA-based COVID-19 immunization in the IA population.